2000
DOI: 10.1021/bi000733w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-CH→NH Substitution in C8-CoA on the Kinetics of Association and Dissociation of Ligands with Medium Chain Acyl-CoA Dehydrogenase

Abstract: We previously reported that the kinetic profiles for the association and dissociation of functionally diverse C(8)-CoA-ligands, viz., octanoyl-CoA (substrate), octenoyl-CoA (product), and octynoyl-CoA (inactivator) with medium chain acyl-CoA dehydrogenase (MCAD), were essentially identical, suggesting that the protein conformational changes played an essential role during ligand binding and/or catalysis [Peterson, K. L., Sergienko, E. E., Wu, Y., Kumar, N. R., Strauss, A. W., Oleson, A. E., Muhonen, W. W., Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…In MCAD, Glu376 is located on loop JK, while in long chain acyl‐CoA dehydrogenase (LCAD) and isovaleryl‐CoA dehydrogenase (i3VD) a corresponding Glu is placed at position 255 on the adjacent helix G, the overall topology at the active center being conserved (see discussion in the accompanying paper [5]). A Glu376Asp mutation in MCAD shows ≈ 5% of the activity of the wild‐type (wt) form [63,64]. This difference was attributed to the nonoptimal positioning of the base in the Asp case.…”
Section: A Carboxylate Glu376‐coo‐ Is the Base Involved In αC‐h Absmentioning
confidence: 99%
“…In MCAD, Glu376 is located on loop JK, while in long chain acyl‐CoA dehydrogenase (LCAD) and isovaleryl‐CoA dehydrogenase (i3VD) a corresponding Glu is placed at position 255 on the adjacent helix G, the overall topology at the active center being conserved (see discussion in the accompanying paper [5]). A Glu376Asp mutation in MCAD shows ≈ 5% of the activity of the wild‐type (wt) form [63,64]. This difference was attributed to the nonoptimal positioning of the base in the Asp case.…”
Section: A Carboxylate Glu376‐coo‐ Is the Base Involved In αC‐h Absmentioning
confidence: 99%
“…The microcalorimetric titration data for the binding of octenoyl‐CoA to MCAD yielded the average values of n , ΔG°, ΔH°, and TΔS° to be 0.98 ± 0.06, −8.3 ± 0.2 kcal/mole, −17.2 ± 1.6 kcal/mole, and −8.9 ± 1.8 kcal/mole, respectively (Peterson et al 1998). A comparative account of these data reveals that whereas the magnitudes of n and ΔG° for the binding of 2‐azaoctanoyl‐CoA are similar to those obtained for the binding of octenoyl‐CoA, the ΔH° and TΔS° values are considerably different (Peterson et al 2000). Of the latter parameters, the ΔH° and TΔS° values for the binding of 2‐azaoctanoyl‐CoA to MCAD are 4.5 and 4.1 kcal/mole more negative, respectively, (i.e., enthalpically more favorable, but entropically less favorable) than those obtained for the binding of octenoyl‐CoA to the enzyme.…”
Section: Resultsmentioning
confidence: 82%
“…We recently undertook a comparative transient kinetic investigation for the binding of octenoyl‐CoA and 2‐azaoctanoyl‐CoA (a redox inactive ligand in which the α‐CH group is replaced by NH) via the stopped‐flow method (Peterson et al 2000). Such studies revealed that although the above substitution did not influence the overall binding affinity of the ligands to the enzyme, it influenced the microscopic steps during the overall binding process (Peterson et al 2000).…”
mentioning
confidence: 99%
See 2 more Smart Citations